How to avoid unsustainable side effects of managing climate risk in drylands — The supplementary feeding controversy. (October 2015) - Müller, Birgit; Schulze, Jule; Kreuer, David; Linstädter, Anja; Frank, Karin
Abstract: The increase in climate risk is of great concern in drylands. Providing livestock with supplementary fodder has become a widely used strategy for coping with this risk. However, its application is controversial. On the one hand, this form of supplementation allows smallholders to avoid a breakdown in animal numbers in times of drought. On the other hand, it keeps herd sizes high and may thus result in rangeland degradation in the long term. This study aims to tackle the question: can supplementary feeding strategies be designed in such a way that they help to reduce livestock asset risk, but avoid or at least reduce unsustainable side effects on pastures? We constructed a stylized ecological–economic simulation model parameterized to a Moroccan case study which incorporates feedbacks between management and vegetation–livestock dynamics under stochastic rainfall. Three supplementation strategies are compared. Furthermore, the impact of socio-economic and climatic change processes, such as price increases for supplementary fodder or rising fluctuations in rainfall, is investigated. Our results show that the conventional supplementation strategy, which supplements in years of forage shortage, reduces livestock asset risk in the short term. However, it can lead to lower pasture productivity and lower yields from pastoralism in the long run. In contrast, a hypothetical strategy which additionally supplements in the year after a drought in order to rest the pasture reduces livestock asset risk and maintains pastures in a better condition without increasing the amount of supplementation. On the methodological level, this study shows the potential of ecological–economic models to assess new management strategies under different processes of global change. Highlights: Supplementary feeding of livestock during droughts is common, but controversial. We use an ecological–economic simulation model to assess supplementation strategies. Conventional strategy may lead to ecological & economic degradation in the long run. New strategies allow regeneration of pasture and protect key livestock asset.